4(-11)+x(3x-4)-6(x+6)=y

Simple and best practice solution for 4(-11)+x(3x-4)-6(x+6)=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-11)+x(3x-4)-6(x+6)=y equation:


Simplifying
4(-11) + x(3x + -4) + -6(x + 6) = y

Multiply 4 * -11
-44 + x(3x + -4) + -6(x + 6) = y

Reorder the terms:
-44 + x(-4 + 3x) + -6(x + 6) = y
-44 + (-4 * x + 3x * x) + -6(x + 6) = y
-44 + (-4x + 3x2) + -6(x + 6) = y

Reorder the terms:
-44 + -4x + 3x2 + -6(6 + x) = y
-44 + -4x + 3x2 + (6 * -6 + x * -6) = y
-44 + -4x + 3x2 + (-36 + -6x) = y

Reorder the terms:
-44 + -36 + -4x + -6x + 3x2 = y

Combine like terms: -44 + -36 = -80
-80 + -4x + -6x + 3x2 = y

Combine like terms: -4x + -6x = -10x
-80 + -10x + 3x2 = y

Solving
-80 + -10x + 3x2 = y

Solving for variable 'x'.

Combine like terms: y + -1y = 0
-80 + -10x + 3x2 + -1y = 0

The solution to this equation could not be determined.

See similar equations:

| 78=-2m+6+m | | 2(3x-4)=5x-6 | | 3x-1=-8+8x | | 3x-33=15 | | 7x+25=235 | | 122+32+n=180 | | -1x+4=8.0 | | =19-15(-9+17k) | | 8-81+-2n=-75 | | x+3=-x+7 | | -5x+10=2x+31 | | 7+25x=235 | | 6=-x+4x | | 3x+5x-10=10x+5x+10-20 | | 1200-870-30x=11 | | 13x^2y^2+39x^4y= | | 8b^2+16b=0 | | 1.5f=8 | | 1.5f= | | 25x+7=235 | | 10a+-7+9=-26 | | -2.5(c+6)=3g-6g | | 50+0.10=0.18m | | -6-8(4n+8)=2(1-4n) | | -2x+15=20 | | 2x^4-5x^3-3x^2+x=0 | | (7+i)(6-9i)= | | a-2+5a=22 | | 11xy^6+77x^3y^4= | | -3x^2+42=0 | | 12+7b=6b | | 4.2=7Z+2.8 |

Equations solver categories